Effects of photobiomodulation therapy on guided bone regeneration in defects filled by biphasic calcium phosphate associated with fibrin biopolymer - Coletta, Bruna Botteon Della (2020)
Bone tissue has an intrinsic regenerating property and can be renewed without any intervention. However, depending on the size of the lesion, as a result of trauma, modifications, tumors, necrosis, the repair may be impaired, requiring bone substitutes to assist in the remodeling process. As a result, interest in research in the area of tissue engineering grew in order to develop biomaterials and capable rehabilitation methods to facilitate the growth of new bone. Thus, the objective of this work was to present an experimental research article to evaluate the effects of laser photobiomodulation therapy on the guided bone regeneration process in rats\' skullcap defects, filled with a hydroxyapatite and beta biomaterial compound tricalcium phosphate associated with the heterologous fibrin three-dimensional biopolymer scaffold. Thirty male Wistar rats were used, randomly separated into three groups: BMG (n = 10), with defects filled with biomaterial and covered by membrane; BFMG (n = 10), with defects filled with biomaterial and fibrin biopolymer, covered by membrane, and BFMLG (n = 10), with defects filled with biomaterial and fibrin biopolymer, covered by membrane and biostimulated with laser. The animals were euthanized at 14 and 42 days after the operation. Through microtomography analyzes and histological images stained by Masson\'s trichrome and hematoxylin and eosin, it was possible to observe that this is a critical size defect, as there was no complete closure of the surgical area by bone tissue, and all groups, at the end of the experimental period, they showed particles of the biomaterial. Histomorphometrically, all groups showed an exponential increase in bone neoformation, however the group with associated biomaterials together with laser photobiomodulation therapy, GBFML, showed a more evident increase. In the analysis of the birefringence of collagen fibers, all groups showed deposition of collagen fibers throughout the experimental period, with a color transition to yellow-green after the 42 days, characterized by the lamellar bone. It is concluded that the results of the present study show that a laser photobiomodulation therapy provided positive effects on guided bone regeneration when associated with fibrin biopolymer and biphasic calcium phosphate, accelerating the remodeling process in critical rats calvaria defects.